Perbandingan Sari Kurma (Phoenix Dactylifera) Campur Air dan Sport Energy Gel Campur Air terhadap Kadar Gula Darah Atlet Kop Hoki Universitas Negeri Jakarta - Ahmad Syauqi; Marco Ariono; Dzulfiqar Diyananda (Faculty of Sports Sciences, Universitas Negeri Yogyakarta, 2025)
Background: Glucose availability affects athlete performance, while fatigue can decrease it. One way to prevent fatigue and maintain performance is by consuming high-carbohydrate drinks. This study aims to analyze the effect of date palm juice and sports drink energy gel x on glucose levels. Methods: This study used a three-period double-blind cross-over design in Hall B, Jakarta State University, involving 10 healthy KOP Hockey athletes from Jakarta State University. Each period, participants underwent a moderate-intensity match with glucose measurements at 0, 20, 40, and 45 minutes. Between periods were separated by a 7-day washout to see significant differences between treatments. Results: Both types of carbohydrate drinks had no significant difference in carbohydrate content. Differences were considered significant if the value (P < 0.05). In treatment groups I and II, there was a significant difference in glucose levels between the 20th and 40th minutes, and between the 20th and 45th minutes, with a P value = 0.001 in group I. Conclusion: Both administration of date palm juice (phoenix dactylifera) mixed with water, and sports drink energy gel x had a significant effect on increasing blood glucose levels in the Jakarta State University hockey team. Keywords: dates extract, sport drink energy gel, blood glucose